An overview of the slope monitoring program at the Serra Sul Iron Ore Project, S11D, northern Brazil - Souza, M.F.; Friguetto, E.; Souza, W.J.; Castro, A.H.C.R. (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
The Serra Sul Iron Ore Project, located in state of Pará, northern Brazil, is one of the largest mining complexes in Vale S.A.’s, history with state-of-the-art mining technology. Operations began in 2017, which saw the application of conveyor systems as the replacement for traditional haul trucks for open pit mining. Ore and waste are transported from mining faces, to the processing plant and waste dumps respectively by conveyor belts. As the mine is ramping up production and the mining area is still on a plateau, slope monitoring at Serra Sul is focussed especially on slopes and soil embankments built to carry a road for conveyor infrastructure. The project has approximately 37 km of conveyors that are assembled on top of cut-and-fill slopes. They are monitored through satellite-based interferometric synthetic aperture radar (InSAR), prism monitoring and visual inspections—on foot and using an unmanned aerial vehicle (drone). An overview of the geotechnical monitoring program and methods used at Serra Sul, the locations of the currently monitored areas, and an analysis of the dataset collected will be presented in this paper.